Cotransfected human chondrocytes: over-expression of IGF-I and SOX9 enhances the synthesis of cartilage matrix components collagen-II and glycosaminoglycans - Simental Mendía, M.; Lara Arias, Jorge; Alvarez Lozano, E.; Said Fernández, S.; Soto Domínguez, A.; Padilla Rivas, Gerardo Raymundo; Martínez Rodríguez, Herminia Guadalupe (Asociación Brasileña de Divulgación Científica, 2015)
Damage to cartilage causes a loss of type II collagen (Col-II) and glycosaminoglycans (GAG). To restore the original cartilage architecture, cell factors that stimulate Col-II and GAG production are needed. Insulin-like growth factor I (IGF-I) and transcription factor SOX9 are essential for the synthesis of cartilage matrix, chondrocyte proliferation, and phenotype maintenance. We evaluated the combined effect of IGF-I and SOX9 transgene expression on Col-II and GAG production by cultured human articular chondrocytes. Transient transfection and cotransfection were performed using two mammalian expression plasmids (pCMV-SPORT6), one for each transgene. At day 9 post-transfection, the chondrocytes that were overexpressing IGF-I/SOX9 showed 2-fold increased mRNA expression of the Col-II gene, as well as a 57% increase in Col-II protein, whereas type I collagen expression (Col-I) was decreased by 59.3% compared with controls. The production of GAG by these cells increased significantly compared with the controls at day 9 (3.3- vs 1.8-times, an increase of almost 83%). Thus, IGF-I/SOX9 cotransfected chondrocytes may be useful for cell-based articular cartilage therapies.